Electrodeposition of CoxNiy Thin Film and Its Catalytic Activity for Ethanol Electrooxidation - Hilman Syafei; Dwi Giwang Kurniawan (Pusat Inovasi Sains, 2023)
Platinum is often used as a catalyst in ethanol electrooxidation. Still, it has many disadvantages being expensive and its active site can be poisoned by CO. Transition metal of Co and Ni can become a catalyst in alcohol electrooxidation at a lower cost to synthesize. In this work, bimetallic CoNi were successfully prepared by electrodeposition method with different Co/Ni ratios to enhance ethanol electrooxidation. Samples of CoNi are characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray (EDX), and electrochemical impedance spectroscopy (EIS). XRD diffractogram confirmed the formation of CoNi. Morphology of CoNi in SEM characterization showed that CoNi with ratio 5:1 has the more dispersed particle and the greatest surface area. EDX characterization indicated that the relative weight of different Co/Ni ratios, the composition wt.% Co is 81.15% and wt.% Ni is 18.85% in CoNi 5:1, wt.% Co is 60.96% and wt.% Ni is 30.94% in CoNi 2:5, while wt.% Co is 50.19%, and wt.% Ni is 49.81% in CoNi 5:5. EIS characterization showed that CoNi with ratio of 5:1 has faster electron kinetics. Electrooxidation of ethanol used cyclic voltammetry (CV) method. The best results from the ethanol electrooxidation reaction were obtained for CoNi with a ratio of 5:1 because of the greatest surface area that showed in scanning electron microscopy and fast electron transfer kinetics compared to others ratio of CoxNiy.